CRISPR/Cas9-mediated TGFβRII disruption enhances anti-tumor efficacy of human chimeric antigen receptor T cells in vitro - Khadijeh Alishah (BMC, 2021)
Abstract Background CAR T-cell therapy has been recently unveiled as one of the most promising cancer therapies in hematological malignancies. However, solid tumors mount a profound line of defense to escape immunosurveillance by CAR T-cells. Among them, cytokines with an inhibitory impact on the immune system such as IL-10 and TGFβ are of great importance: TGFβ is a pleiotropic cytokine, which potently suppresses the immune system and is secreted by a couple of TME resident and tumor cells. Methods In this study, we hypothesized that knocking out the TGFβ receptor II gene, could improve CAR T-cell functions in vitro and in vivo. Hereby, we used the CRISPR/Cas9 system, to knockout the TGFβRII gene in T-cells and could monitor the efficient gene knock out by genome analysis techniques. Next, Mesothelin or Claudin 6 specific CAR constructs were overexpressed via IVT-RNA electroporation or retroviral transduction and the poly-functionality of these TGFβRII KO CAR T-cells in terms of proliferation, cytokine secretion and cytotoxicity were assessed and compared with parental CAR T-cells. Results Our experiments demonstrated that TGFβRII KO CAR T-cells fully retained their capabilities in killing tumor antigen positive target cells and more intriguingly, could resist the anti-proliferative effect of exogenous TGFβ in vitro outperforming wild type CAR T-cells. Noteworthy, no antigen or growth factor-independent proliferation of these TGFβRII KO CAR T-cells has been recorded. TGFβRII KO CAR T-cells also resisted the suppressive effect of induced regulatory T-cells in vitro to a larger extent. Repetitive antigen stimulation demonstrated that these TGFβRII KO CAR T-cells will experience less activation induced exhaustion in comparison to the WT counterpart. Conclusion The TGFβRII KO approach may become an indispensable tool in immunotherapy of solid tumors, as it may surmount one of the key negative regulatory signaling pathways in T-cells.